Pengembangan Buku Saku Berdasarkan Studi Identifikasi Tanaman Obat Pada Masyarakat Suku Serawai Bengkulu Selatan - Rio Sunardi; Dewi Handayani; Wiwit Wiwit (ALOTROP, 2023)
This research is a research and development of teaching materials in the form of a pocketbook based on the study of the identification of medicinal plants in the Serawai people of South Bengkulu. The purpose of this study was to determine the medicinal plants, the content of secondary metabolite phytochemical compounds in each plant, and the validity and responses of students to the developed pocketbook. The development model used is the research and development (R&D) model of Bord and Gall (1983) which is limited to the seventh stage, namely the revision of the product from the limited trial results. From the research, 19 (nineteen) medicinal plants were selected that were used by the Serawai people of South Bengkulu. The results of secondary metabolite screening showed that the medicinal plants found contained various levels of tannins, alkaloids, saponins, flavonoids, terpenoids, and steroids. The validity of the pocketbook from the study of the identification of medicinal plants in the Serawai tribal community obtained an average value of 84.3% for the material aspect and 91.7% for the media aspect which was included in the very appropriate category. Student responses regarding the pocket book of medicinal plants developed obtained a value the percentage of material aspects, media, benefits are 85.8%, 88.0%, and 87.0%, respectively with an average of 86.9% which were included in the very good criteria. Student also give a positive response to the product being developed with a 100 % interest percentage. Keywords: Pocket Book, Medicinal Plants, Serawai Tribe, Secondary Metabolites